CO chemisorption at vacancies of supported graphene films: a candidate for a sensor?. Issue 28 (4th July 2016) - Celasco, E.; Carraro, G.; Lusuan, A.; Smerieri, M.; Pal, J.; Rocca, M.; Savio, L.; Vattuone, L.
Abstract : We investigate CO adsorption at single vacancies of graphene supported on Ni(111) and polycrystalline Cu. Abstract : We investigate CO adsorption at single vacancies of graphene supported on Ni(111) and polycrystalline Cu. The borders of the vacancies are chemically inert but, on the reactive Ni(111) substrate, CO intercalation occurs. Adsorbed CO dissociates at 380 K, leading to carbide formation and mending of the vacancies, thus preventing their effectiveness in sensor applications.